A randomized clinical trial evaluating the efficacy of the sandwich bone augmentation technique in increasing buccal bone thickness during implant placement. II. Tomographic, histologic, immunohistochemical, and RNA analyses. Issue 10 (15th September 2014) - Fu, Jia‐Hui; Rios, Hector; Al‐Hezaimi, Khalid; Oh, Tae‐Ju; Benavides, Erika; Wang, Hom‐Lay
Abstract Objectives This study aimed to evaluate the biologic and structural phenotypes of the bone regenerated via the sandwich bone augmentation (SBA) technique, on buccal implant dehiscence defects. Material and Methods Twenty‐six patients with one buccal implant dehiscence defect each were randomly assigned to two groups. Both groups received a standardized amount of mineralized cancellous and cortical allogenic bone graft. In the test group, a bovine pericardium membrane was placed over the graft, while no membrane was placed in the control group. After 6 months of healing, a bone core biopsy of the regenerated bone was harvested and processed for histologic, immunohistochemical, mRNA, and micro‐computed tomography (μCT) analyses. Of the 26 bone core biopsies, only six cores from the test group and six cores from the control group were suitable for the analysis. Results Bone volume (BV) in the test group was maintained, but tissue maturation appeared to be delayed. In contrast, tissue maturation appeared to be completed in the control group, but BV was compromised. Micro‐CT analysis showed that specimens from the control group were more structured and mineralized compared with those from the test group. Histologic analysis showed more residual graft particles scattered in a loose fibrous connective tissue matrix with sparse bone formation in the test group, while the control group showed obvious vital bone formation surrounding the residual graft particles. Positive periostin (POSTN), sclerostin, and runt‐related transcription factor‐2 (RUNX2) immunoreactivities were detected in both the control and test groups. However, tartrate‐resistant acid phosphatase (TRAP) positive was mostly noted in the control group. There were significant differences in POSTN, RUNX2 and VEGF expressions between the test and control groups. Conclusion These findings indicated that the SBA technique was an effective method in preserving adequate structural volume while promoting new vital bone formation. Use of the collagen barrier membrane has successfully maintained the volumetric dimensions of the ridge but might have slowed down the complete maturation of the outermost layer of the grafted site.